Copper-uptake is critical for the down regulation of synapsin and dynamin induced by neocuproine: modulation of synaptic activity in hippocampal neurons - Castro, Patricio A.; Ramirez, Alejandra; Sepúlveda, Fernando J.; Peters, Christian; Fierro, Humberto; Waldron, Javier; Luza, Sandra; Fuentealba, Jorge; Muñoz, Francisco J.; De Ferrari, Giancarlo V.; Bush, Ashley I.; Aguayo, Luis G.; et al. (Frontiers in Aging Neuroscience, 2014)
Extracellular and intracellular copper and zinc regulate synaptic activity and synaptic plasticity, which may impact brain functionality and human behavior. We have found that a metal coordinating molecule, Neocuproine, transiently increases free intracellular copper and zinc levels (i.e. min) in hippocampal neurons as was monitored by Phen Green and FluoZin-3 fluorescence, respectively. The changes in free intracellular zinc induced by Neocuproine were abolished by the presence of a non-permeant copper chelator, Bathocuproine, indicating that copper influx is needed for the action of Neocuproine on free intracellular Zn levels. Moreover, Neocuproine decreased the mRNA levels of Synapsin and Dynamin, but not mRNA for Bassoon, tubulin or superoxide dismutase. Western blot analysis showed that protein levels of synapsin and dynamin were also decreased in the presence of Neocuproine. Furthermore, these changes were accompanied by a decrease in neuronal activity as was determined by calcium transient measurements. Neocuproine decreased the number of active neurons, effect that was blocked by the presence of Bathocuproine, indicating that copper influx is needed for the action of Neocuproine. Moreover, Neocuproine blocks the epileptiform activity induced by bicuculline in hippocampal neurons. This data indicate that presynaptic protein configuration and function of primary hippocampal neurons is sensitive to transient changes in transition metal homeostasis. Therefore, small molecules able to coordinate transition metals and penetrate the blood-brain barrier might modify neurotransmission at the Central Nervous System. This can be useful to establish therapeutic approaches to control the neuronal hyperexcitabiltity observed in brain conditions that are associated to brain copper dyshomeotasis such as Alzheimer’s and Menkes diseases. This work also opens a new avenue to find novel and effective antiepilepsy drugs based in metal coordinating molecules.